EFFECT OF ANTIOXIDANTS AND PACKING CONDITIONS ON STORAGE STABILITY OF CEREAL BAR FORTIFIED WITH HYDROLYZED COLLAGEN FROM SEABASS SKIN - BENJAKUL, S.; PISUCHPEN, S.; O'BRIEN, N.; KARNJANAPRATUM, S. (Italian Journal of Food Science, 2018)
Effect of antioxidants (green tea powder (GT) and citric acid (CA)) and packing conditions on storage stability of cereal bar fortified with hydrolyzed collagen (HC) from seabass skin was studied up to 6 months of storage at 25°C in dark. Up to 3 months of storage, the addition of antioxidants impeded lipid oxidation, especially those cereal bars packed in polypropylene with normal heat seal (PP). Changes in moisture content, water activity, color, texture, PV, TBARS and formation of volatiles were effectively retarded when samples were packed under N2 gas in laminated polyethylene/aluminium foil bag (LF) for 6 months of storage.